The Holy Dormition Kyiv-Pechersk Lavra in the travel notes of English travelers of the first half of the 19th century - Pysarevskyi , Oleksandr (Young Scholars Grinchenko – Seton International Journal, 2025)
In the first half of the 19th century, Kyiv attracted the attention of travelers from different countries. Their travelogues depicted it as a multidimensional phenomenon, harmoniously combining monumental architecture, a rich spiritual life, and a unique social order. Sacred architecture occupied a special place in their perception of the city – it became a lens through which observers comprehended Kyiv's cultural and historical essence. The study of the significance of sacred architecture in shaping the image of the city in travelogues is relevant, as it allows for a better understanding of the cultural heritage of Kyiv and the peculiarities of intercultural dialogue at that time. The study of the representation of Kyiv in travelogues was carried out by various authors who analyzed travelogues as a source of historical and ethnographic information. Foreign researchers paid attention to Kyiv.